Вплив нейротехнологій та цінових прийомів мерчандайзингу на поведінку споживачів - Капінус, Лариса Василівна; Скригун, Наталія Петрівна; Молін, Наталія Олегівна (My University, 2022)
Статтю присвячено розгляду існуючих психологічних методів та цінових прийомів нейромаркетингу та їхнього впливу на поведінку споживачів. Розглянуто необхідність вивчення такого критерію, як вплив кольору на покупців з точки зору збільшення обсягів продажу товарів. Наведено визначення нейромаркетингу відповідно до різних сфер науки, та, зокрема, стосовно маркетингової діяльності. Описано історію розвитку нейромаркетингових досліджень: які теорії панували до моменту формування цього напрямку та які вчені сприяли його розвитку. Визначено цілі та завдання нейромаркетингу, а також описано тригери, які впливають на підсвідомість споживачів. Розглянуто методи впливу на поведінку споживачів. Також висвітлено різні точки зору щодо використання результатів нейромаркетингових досліджень у діяльності підприємств. Визначено мерчандайзингові нейропсихологічні цінові прийомі, які стимулюють мозок споживачів та підштовхують до прийняття рішення про купівлю товарів. Marketers at all times have sought to look into the heads of consumers to find out the answers to their questions – what and how people choose in a particular category of products. But it was possible to do this only with the emergence of a separate direction, which was called neuromarketing. Thanks to neuromarketing research, it is possible to constantly develop and increase the effectiveness of marketing. This direction allows you to develop the most effective advertising model for a particular company. The history of the development of neuromarketing research is described, which theories prevailed until the formation of this direction and which scientists contributed to its development. The differences between neuromarketing research and those used in classical marketing are described. It is concluded that the most optimal option is the integrated use of research data. It has been determined that only large companies can afford to create their own divisions to conduct the relevant research. Since the maintenance of suchstructureit requires quite a lot of finance. The goals and objectives of neuromarketing, as well as triggers, which are the main ones for influencing the subconscious of consumers, have been determined. The ways of influencing on consumer behavior are described. It also reflects different points of view on the use of the results of neuromarketing research in the companies’activities. It was determined that neuromarketing is a fairly promising method for determining the effectiveness of advertising messages, which is already used by leading companies.
Keywords: кафедра маркетингу; нейромаркетинг; нейромаркетингові дослідження; поведінка споживачів; стимули; підсвідомість споживачів; neuromarketing; neuromarketing research; consumer behavior; incentives; consumer subconscious